Ecologies of empire in South Asia, 1400-1900 - Guha, Sumit (Seattle : University of Washington Press, 2023)
"By focusing on the human gaze, or how people interpret their relationship with land, Sumit Guha traces the longue durée of the political ecology of empire in South Asia during the age of empires. This relationship is in most sharp relief when comparing the exploitative and extractive practices of the Mughal Empire and the industrial British Raj as these imperial regimes encountered a large and old agrarian society. While scholars of South Asia regularly dwell on the destructive nature of British policies in South Asia, Guha integrates the cultural turn in environmental studies with the complex imperial rivalries that defined South Asia from the fifteenth through the mid-twentieth century to demonstrate how land use is defined through matrices of competing geographic expertise, too often in service of distant courts and environmental degradation"--
Inequality, complexity, and ecology -- South Asia in the imperial gaze -- Imperial gaze, lordly grasp -- The village and its inhabitants -- Lands of resistance, terrains of refuge -- Colonialism, disarmament, and the closing of the forest frontier.
Includes bibliographical references and index.
Keywords: Human ecology -- South Asia; Landscapes -- Social aspects -- South Asia; Land use -- Social aspects -- South Asia; Human beings -- Effect of environment on -- South Asia; South Asia -- Social life and customs